Improving Performance Based on Work Engagement and Organizational Citizenship Behavior in the Hospital Services Industry - Niwidadi, Sri Rahayu; Nuryadi, Nuryadi; Beni K, Muhammad Sifak; Abdillah, Yusuf; Qomariah, Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Improving performance is an important thing that must get the attention of every organization in facing increasing competition today, so that it can compete openly. This research design aims to determine the impact of work engagement and organizational citizenship behavior on employee performance in the hospital industry in Jember Regency. The population in this study were all nurses who worked in the inpatient department. The sample size was determined to be 117 nurses with the provisions for regional research being sufficient. The analysis design used is descriptive analysis, validity and reliability tests and research hypothesis testing. The results of this research are expected to show that work engagement and organizational citizenship behavior can improve employee performance in the hospital industry in Jember Regency.